miR-548d-3p Alters Parasite Growth and Inflammation in Leishmania (Viannia) braziliensis Infection - Souza, Marina de Assis; Ramos-Sanchez, Eduardo Milton; Muxel, Sandra Márcia; Lagos, Dimitris; Reis, Luiza Campos; Pereira, Valéria Rêgo Alves; Brito, Maria Edileuza Felinto; Zampieri, Ricardo Andrade; Kaye, Paul Martin; Floeter-Winter, Lucile Maria; Goto, Hiro (Frontiers in Cellular and Infection Microbiology, 2021)
American Tegumentary Leishmaniasis (ATL) is an endemic disease in Latin America, mainly caused in Brazil by Leishmania (Viannia) braziliensis. Clinical manifestations vary from mild, localized cutaneous leishmaniasis (CL) to aggressive mucosal disease. The host immune response strongly determines the outcome of infection and pattern of disease. However, the pathogenesis of ATL is not well understood, and host microRNAs (miRNAs) may have a role in this context. In the present study, miRNAs were quantified using qPCR arrays in human monocytic THP-1 cells infected in vitro with L. (V.) braziliensis promastigotes and in plasma from patients with ATL, focusing on inflammatory response-specific miRNAs. Patients with active or self-healed cutaneous leishmaniasis patients, with confirmed parasitological or immunological diagnosis, were compared with healthy controls. Computational target prediction of significantly-altered miRNAs from in vitro L. (V.) braziliensis-infected THP-1 cells revealed predicted targets involved in diverse pathways, including chemokine signaling, inflammatory, cellular proliferation, and tissue repair processes. In plasma, we observed distinct miRNA expression in patients with self-healed and active lesions compared with healthy controls. Some miRNAs dysregulated during THP-1 in vitro infection were also found in plasma from self-healed patients, including miR-548d-3p, which was upregulated in infected THP-1 cells and in plasma from self-healed patients. As miR-548d-3p was predicted to target the chemokine pathway and inflammation is a central to the pathogenesis of ATL, we evaluated the effect of transient transfection of a miR-548d-3p inhibitor on L. (V.) braziliensis infected-THP-1 cells. Inhibition of miR-548d-3p reduced parasite growth early after infection and increased production of MCP1/CCL2, RANTES/CCL5, and IP10/CXCL10. In plasma of self-healed patients, MCP1/CCL2, RANTES/CCL5, and IL-8/CXCL8 concentrations were significantly decreased and MIG/CXCL9 and IP-10/CXCL10 increased compared to patients with active disease. These data suggest that by modulating miRNAs, L. (V.) braziliensis may interfere with chemokine production and hence the inflammatory processes underpinning lesion resolution. Our data suggest miR-548d-3p could be further evaluated as a prognostic marker for ATL and/or as a host-directed therapeutic target.